2016
DOI: 10.1186/s12935-016-0310-9
|View full text |Cite
|
Sign up to set email alerts
|

A humanized anti-CD26 monoclonal antibody inhibits cell growth of malignant mesothelioma via retarded G2/M cell cycle transition

Abstract: BackgroundMalignant Mesothelioma (MM) is a highly aggressive tumor with poor prognosis. Multimodal treatments and novel molecular targeted therapies against MM are in high demand in order treat this disease effectively. We have developed a humanized monoclonal antibody YS110 against CD26 expressed in 85 % of MM cases. CD26 is thought to be involved in tumor growth and invasion by interacting with collagen and fibronectin, or affecting signal transduction processes.MethodsWe evaluated the direct anti-tumor effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We will investigate the relationship between CD26 expression or other biomarkers and clinical outcome of YS110. YS110 has been found to induce MPM cell lysis via antibody-dependent cytotoxicity [12,15,23]. It has also been shown to induce cell cycle arrest in CD26 + malignant mesothelioma cells and to control the growth of MPM cells via up-regulation of the cyclin-dependent kinase inhibitors p21 or p27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will investigate the relationship between CD26 expression or other biomarkers and clinical outcome of YS110. YS110 has been found to induce MPM cell lysis via antibody-dependent cytotoxicity [12,15,23]. It has also been shown to induce cell cycle arrest in CD26 + malignant mesothelioma cells and to control the growth of MPM cells via up-regulation of the cyclin-dependent kinase inhibitors p21 or p27.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive in vitro and in vivo studies have shown that YS110 possesses antitumor activity for malignant mesothelioma cell lines. [11,15] Single or repeated intravenous administration of YS110 has also been found to be safe in nonhuman primates. [16] The first phase I study of YS110 in humans was conducted in France and found that its administration at doses up to 6 mg/kg weekly was generally well tolerated and showed promising efficacy in 33 patients with advanced or refractory CD26expressing tumors including malignant mesothelioma, renal cell carcinoma, and urothelial carcinoma [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular localization analysis revealed that YS110 caused an increase in transport via caveolin-dependent endocytosis and accumulation of CD26 to the nucleus of MPM resulting in suppression of POLR2 gene expression and subsequent growth suppression of MPM cells, while highlighting a secondary anti-tumor mechanism of anti-CD26 mABs [ 96 , 97 ]. Meanwhile, a recently published paper demonstrated that YS110 caused retarded G2/M cell cycle progression through inhibition of phosphorylation of cdc2 and cdc25C and activation of ERK1/2 [ 98 ]. Importantly, a synergistic effect between YS110 and the first line anti-MPM chemotherapeutic agent pemetrexed was observed, as the combination of YS110 and pemetrexed showed superior anti-tumor activity associated with combinatorial G1/S and G2/M cell cycle transition inhibition than either agent alone in a mouse xenograft model of MPM [ 98 ].…”
Section: Potential Approach To Targeting Cd26 In Mpmmentioning
confidence: 99%
“…Meanwhile, a recently published paper demonstrated that YS110 caused retarded G2/M cell cycle progression through inhibition of phosphorylation of cdc2 and cdc25C and activation of ERK1/2 [ 98 ]. Importantly, a synergistic effect between YS110 and the first line anti-MPM chemotherapeutic agent pemetrexed was observed, as the combination of YS110 and pemetrexed showed superior anti-tumor activity associated with combinatorial G1/S and G2/M cell cycle transition inhibition than either agent alone in a mouse xenograft model of MPM [ 98 ].…”
Section: Potential Approach To Targeting Cd26 In Mpmmentioning
confidence: 99%
“…The active antimesothelioma agent PEM rapidly induces CD26 expression on the cell surface and inhibits in vivo tumor growth synergistically with YS110 [14]. The mechanisms of YS110 antitumor action for CD26-positive mesotheliomas are the following: (a) cell lysis of MPM cells via antibody-dependent cell-mediated cytotoxicity in addition to its direct antitumor effect via cyclin-dependent kinase (CDK) inhibitor p27 kip1 upregulation and disruption of binding to ECM [13]; (b) G1/S cell cycle arrest and G2/M cell cycle delay by upregulating CDK inhibitor p27 kip1 and p21 cip/ waf1 via multiple signaling pathways [13][14][15]; and (c) induction of nuclear translocation of cell-surface CD26 molecules by internalization of the CD26-YS110 complexes to inhibit proliferation of MPM cells via suppression of POLR2A gene expression [16]. The reduction of distant metastases by YS110 treatment in experimental models may be explained by CD26's function as a binding protein to distinct ECM proteins [13].…”
Section: Humanized Anti-cd26 Monoclonal Antibody (Ys110) For the Treamentioning
confidence: 99%